Deutsche, merkt aus und erkennt. (Danzig : [s.n., 1918)
Druk dot. gen. Ludendorffa i bitwy pod Tannenbergiem (1914).
Data wyd. na podst. treści.
Keywords: Ludendorff, Erich -- (1865-1937).; Tannenberg, Bitwa (1914) -- druki ulotne; Wojna światowa (1914-1918) -- Niemcy -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne